Mejni model v slovenski religiozni poeziji - Bernik, France (Primerjalna književnost, 2006)
A Limit Model in Slovenian Religious Poetry. The author deals with the problem of a special thematic group of the Slovenian poetic art, the religious poetry, which was of no particular interest to the professional and other public until now, and was almost forgotten or kept secret in the last half-century. The author is interested in diverse expressions of religious emotions and consciousness, in dynamics of the basic static world view as manifested in the 19th and 20th century Slovenian poetry. But above all, the author asks himself which are the religious poems that with their confessional contents reach the very limit of their theme, the limit that could not be pushed further anymore.
Keywords: slovenska poezija; religiozna poezija; religiozne teme; Christianity; krščanstvo